Sja‐miR‐71a in Schistosome egg‐derived extracellular vesicles suppresses liver fibrosis caused by schistosomiasis via targeting semaphorin 4D - Lifu Wang; Yao Liao; Ruibing Yang; Zilong Yu; Lichao Zhang; Zifeng Zhu; Xiaoying Wu; Jia Shen; Jiahua Liu; Lian Xu; Zhongdao Wu; Xi Sun (2020)
Schistosomiasis is characterized by liver fibrosis, and studies have indicated that Schistosoma japonicum (S. japonicum) eggs can limit the progression of liver fibrosis. However, the detailed molecular mechanisms are yet unclear. Extracellular vesicles (EVs) contain a selection of miRNAs for long-distance exchange of information and act as an important pathway for host-parasite communication. This study aimed to explore the potential role of S. japonicum egg-derived EVs and its key miRNA in liver fibrosis. Herein, we found that S. japonicum egg-derived EVs can inhibit the activation of hepatic stellate cells, which is mediated via the high expression of Sja-miR-71a. Sja-miR-71a in EVs attenuates the pathological progression and liver fibrosis in S. japonicum infection. Sja-miR-71a inhibiting TGF-β1/SMAD and interleukin (IL)-13/STAT6 pathways via directly targeting semaphorin 4D (Sema4D). In addition, Sja-miR-71a can also suppress liver fibrosis by regulating Th1/Th2/Th17 and Treg balance. This study contributes to further understanding of the molecular mechanisms underlying Schistosoma-host interactions, and Sema4D may be a potential target for schistosomiasis liver fibrosis treatment.